2019
DOI: 10.1111/nin.12291
|View full text |Cite
|
Sign up to set email alerts
|

Conceptualising moral resilience for nursing practice

Abstract: The term ‘moral resilience’ has been gaining momentum in the nursing ethics literature. This may be due to it representing a potential response to moral problems such as moral distress. Moral resilience has been conceptualised as a factor that inhibits immoral actions, as a favourable outcome and as an ability to bounce back after a morally distressing situation. In this article, the philosophical analysis of moral resilience is developed by challenging these conceptualisations and highlighting the risks of su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
29
0
4

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(34 citation statements)
references
References 41 publications
1
29
0
4
Order By: Relevance
“…The young people sought to make moral judgements about what was 'right and good' for their family members (Jurchak and Pennington 2009, 78). Similar to caring professionals, their moral actions reflected a desire to provide compassionate care (Jurchak and Pennington 2009;Defilippis, Curtis, and Gallagher 2019). Their caring tasks included chaperoning their family members, monitoring personal care and intervening to protect them from harm.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The young people sought to make moral judgements about what was 'right and good' for their family members (Jurchak and Pennington 2009, 78). Similar to caring professionals, their moral actions reflected a desire to provide compassionate care (Jurchak and Pennington 2009;Defilippis, Curtis, and Gallagher 2019). Their caring tasks included chaperoning their family members, monitoring personal care and intervening to protect them from harm.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, a moral approach to care is not about 'adjudicating ethical dilemmas' but involves acting ethically on behalf of others (Hamington 2018, 310). Engaging in a situated and relational approach to care may have helped to facilitate the young people's moral resilience (Rushton 2016;Defilippis, Curtis, and Gallagher 2019). A previous study of young adult carers in England concluded that the caring role had stimulated their political consciousness (Heyman 2018).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Based on our results gradually, some nurses become morally indifferent. Sala Defilippis et al, 2019 defined moral indifferent persons as one who sees the moral situation and has not any sense about it (61). The results of Choe et al in 2015 showed that nurses became morally indifferent due to high workload and time constraints (62).…”
Section: Discussionmentioning
confidence: 99%